1997
DOI: 10.1029/97gl00920
|View full text |Cite
|
Sign up to set email alerts
|

Observations of ultrafine aerosol particle formation and growth in boreal forest

Abstract: We have measured submicron particles rather continuously since January 31st 1996 at a forest site in Southern Finland. Number size distribution data from the size range of 3-500 nm (particle diameter) are obtained every 10 minutes. This article attemps to give an overall view over diurnal pattern of submicron size distribution. We will show the typical ambient submicron particle size distribution as it is monitored at the site and, furthermore, we want to highlight some certain events that have been observed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
192
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(208 citation statements)
references
References 26 publications
13
192
0
3
Order By: Relevance
“…Using instruments that can detect particles with diameters as low as 3 nm, UFP have been documented in the free troposphere [Clarke et al, 1998;Raes et al, 1997;Schröder and Ström, 1997] and in the vicinity of clouds [Hegg et al, 1991]. Significant evidence of nucleation of new particles was found at continental boundary layer sites [Birmili and Wiedensohler, 2000;Verheggen and Mozurkewich, 2002;Birmili et al, 2003], including boreal forests [Mäkelä et al, 1997;Kulmala et al, 1998Kulmala et al, , 2001aKulmala et al, , 2001bKomppula et al, 2003] and Arctic regions [Wiedensohler et al, 1996;Pirjola et al, 1998]. The marine boundary layer (BL) provided evidence of homogeneous nucleation both in remote sites and near-coastal regions [Covert et al, 1992;Hoppel et al, 1994;Weber et al, 1998;Allen et al, 1999;O'Dowd et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using instruments that can detect particles with diameters as low as 3 nm, UFP have been documented in the free troposphere [Clarke et al, 1998;Raes et al, 1997;Schröder and Ström, 1997] and in the vicinity of clouds [Hegg et al, 1991]. Significant evidence of nucleation of new particles was found at continental boundary layer sites [Birmili and Wiedensohler, 2000;Verheggen and Mozurkewich, 2002;Birmili et al, 2003], including boreal forests [Mäkelä et al, 1997;Kulmala et al, 1998Kulmala et al, , 2001aKulmala et al, , 2001bKomppula et al, 2003] and Arctic regions [Wiedensohler et al, 1996;Pirjola et al, 1998]. The marine boundary layer (BL) provided evidence of homogeneous nucleation both in remote sites and near-coastal regions [Covert et al, 1992;Hoppel et al, 1994;Weber et al, 1998;Allen et al, 1999;O'Dowd et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…[13] Newly formed particles by homogeneous nucleation of water and sulfuric acid, in presence of ammonia and other organic species, tend to have very small sizes (d p $ 2 nm) [Covert et al, 1992;Mäkelä et al, 1997;Marti et al, 1997;Weber et al, 1997Weber et al, , 1998Kulmala et al, 1998;O'Dowd et al, 1999;Clarke et al, 1998]. It has been shown that the nucleation rate can be enhanced by the presence of organics and ions [Yu et al, 1999;Yu and Turco, 2000].…”
Section: Growth Rate Of Ufpmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Two types of nucleation events have been observed in which the main condensing species are not sulfuric acid and ammonia: in Finnish forests [Mäkelä et al, 1997] and off the Irish coast [O'Dowd et al, 1999]. Their characteristics, covering many events, have been explored in large cooperative European campaigns, Biogenic Aerosol Formation in the Boreal Forest (BIOFOR) and New Particle Formation and Fate in the Coastal Environment (PARFORCE), whose results have recently been reported [Kulmala and Hämeri, 2000;O'Dowd and Hämeri, 2000].…”
Section: Previous Workmentioning
confidence: 99%
“…[2] Significantly increased concentrations of ultrafine particles in the size range of a few nanometers in diameter have been observed in the atmosphere at various locations worldwide [e.g., Weber et al, 1997;Covert et al, 1992;Wiedensohler et al, 1996;Mäkelä et al, 1997;O'Dowd et al, 1999]. Although these ultrafine particles appear to be caused by nucleation, the causes of these nucleation events are unclear.…”
Section: Introductionmentioning
confidence: 99%